ANALISIS BEBAN KERJA KELOMPOK PENYELENGGARA PEMUNGUTAN SUARA (KPPS) MENGGUNAKAN METODE FTE (FULL TIME EQUIVALENT) PADA PEMILIHAN UMUM SERETAK TAHUN 2019 DI KABUPATEN BANGKA TENGAH - cecep, Ricky Febriansyah (Komisi Pemilihan Umum, 2019)
The 2019 Simultaneous Elections became a very heavy and broad workload for the Voter Organizer Group (KPPS). This is because KPPS must serve voters as many as 5 (five) ballots. KPPS expenses occur before, voting and counting and afterwards. The weight of the KPPS caused them to be exhausted, thus interfering with the voting and counting process, even causing work accidents such as illness and death. For this reason, work load calculation using the FTE (Full Time Equivalent) method is required. FTE method by dividing the work with real time. This research method is located at TPS 02 Padang Baru Village, Pangkalan Baru Subdistrict, Central Bangka Regency because KPSS has miscalculated so that the ballot box must be opened at the time of plenary at the PPK level (District Voting Committee). The method used by using work sampling in the process of counting votes conducted by KPPS at the TPS. From the FTE calculation results, the KPPS workload is included in the overload category, averaging above 2. With this FTE data as a recommendation for organizing elections so as not to provide a heavy workload for KPPS.